The effect of childhood trauma on bipolar depression - Hernán F. Guillen-Burgos; Juan F. Gálvez-Flórez; Sergio Moreno-López; María C. Solano; Angela T. H. Kwan; Hernando Santamaria-Garcia; Carlos Gómez-Restrepo; Roger S. McIntyre (Scientific Reports)
Abstract Childhood trauma (CT) is associated with an earlier onset and a more severe course of bipolar disorder (BD). However, the specific impact of CT on bipolar depression remains unclear. Herein, this study aimed to investigate the effect of CT using depressive episode frequency as a threshold for disease burden and severity. A cohort of 146 participants with BD was followed for 3 years. The effects of CT on mood episodes, hospital readmissions, suicidal ideation, and behavior were analyzed. A high number of depressive episodes were identified in participants with BD and CT exposure, with the effect being more pronounced in BD II than in BD I. A threshold of ≥4 depressive episodes serves as a sensitivity cutoff point to detect associations with severe outcomes, such as early readmission and suicidal ideation and behavior. The presence of CT increases the risk of experiencing at least one severe outcome by 80%. In our cohort, a cutoff point of ≥4 depressive episodes mediated the effect of CT on at least one severe outcome (early readmission or suicidal ideation and behavior). The study is limited by its non-probabilistic sample, recall bias, and moderate receiver operating characteristic curve value. The findings reinforce the association between CT and BD severity, highlighting the significantly higher number of depressive episodes in individuals with CT. This underscores CT as a risk factor for depressive predominant polarity and more frequent mood episodes in BD.